PERCUTANEOUS TIBIAL NERVE STIMULATION FOR OVERACTIVE BLADDER. Issue 10 (9th September 2014) - Tudor, Katarina Ivana; Seth, Jai; Ochulor, Juliana; Liechti, Martina D; Fox, Zoe; Gonzales, Gwen; Haslam, Collette; Pakzad, Mahreen; Elneil, Sohier; Panicker, Jalesh N
Abstract : Background: Percutaneous Tibial Nerve Stimulation (PTNS) is a minimally invasive neuromodulation technique for treatment of overactive bladder (OAB). The aim of this study was to assess safety and efficacy in neurological patients. Methods: In this prospective evaluation over 18 months at a tertiary centre, patients finding first-line treatments for OAB ineffective or intolerable underwent standard 12-week course of PTNS (Urgent PC, Uroplasty). Symptoms were evaluated using standardised questionnaires (ICIQ-OAB and ICIQLUTS-QoL) and bladder diaries. Results: Of 74 consecutive patients (52 males; mean age 57; 25(33.8%) idiopathic OAB, 19 (25.7%) multiple sclerosis (MS), 30 (40.5%) other neurological conditions), 64(86%) completed treatment. Significant improvements (p<0.05) were noted in OAB scores, quality of life, 24-hour bladder frequency, number/severity of incontinent episodes. Patients found treatment comfortable and no adverse effects were reported. Thirty-two(61.5%) opted to continue; mean top-up interval 44.4 days (7–155 days). Patients reporting improvements in OAB symptoms, leakage severity and quality of life at week 12, as well as patients with MS and other neurological disorders, more often returned for top-up sessions(p<0.05). Conclusions: PTNS is a safe and effective treatment in patients with neurological disorders, associated with significant improvements in overactive bladder symptoms and quality of life.